Respon Dosis Pupuk KCl dan Cekaman Kekeringan pada Pertumbuhan Bibit Kelapa Sawit (Elaeis guineensis Jacq.) di Pembibitan Awal Pre-Nursery - Moh. Syahrul Munir; Titin Andriyni Atmojo; Elis Rahmawati Mar`atus Sholihah; Getta Hayyuning Mangesti (Botani : Publikasi Ilmu Tanaman dan Agribisnis, 2026)
This study aimed to determine the response of oil palm (Elaeis guineensis Jacq.) seedlings to KCl fertilizer dosage and drought stress in the early pre-nursery seedling phase. The experiment used a factorial randomized block design (RBD) with a combination of KCl dosage and soil water content, replicated three times, with observations made on the parameters of corm diameter, leaf width, and number of leaves. The observation data were analyzed using analysis of variance and continued with the Duncan Multiple Range Test (DMRT) at the 5% level if there were significant differences. The results showed that KCl dosage, drought stress, or the interaction of the two did not have a significant effect on corm diameter and number of leaves. Conversely, drought stress individually had a significant effect on leaf width, while KCl dosage showed no significant effect. The interaction between KCl dosage and drought also had no statistical impact on leaf width. These findings indicate that in the pre-nursery phase, oil palm seedling growth in corm diameter and number of leaves was relatively stable across treatments, while leaf width was more sensitive to water limitations. The implications of this study indicate the importance of managing the availability of water in the planting medium to support leaf growth, while the administration of KCl at the tested dose has not provided a significant effect on the initial phase of seedling growth.